LANGUAGE STYLE IN MARIO TEGUH GOLDEN WAYS TALK SHOW - Dahratul Aini and Syamsul Bahri (LINGUISTICA, 2015)
This study deals with the type of language style used in Mario Teguh GoldenWays Talk Show. The objectives of this study are to find out the most types oflanguage style, to describe how the most dominant language style used and toreason for the use of the most dominant language style used by Mario Teguh inMario Teguh Golden Ways Talk Show. The study was conducted by usingdescriptive qualitative method. The data of this research were utterances of MarioTeguh in Mario Teguh Golden Ways Talk Show. The findings of this researchare the most dominant of language used by Mario Teguh in Mario Teguh GoldenWays is consultative style (60.6%) followed by casual style (32.45%), frozen style(5.2%), formal style(1.8%) and intimate style (0%). In this talk show Mario Teguhtends to use consulative style while he was speaking with the participants toprovide more explicit background information of the participant’s problems. Theconsultative style in all context is used to make audiences easily understand howthe topic is going on in their life.